Magnetometric investigation of glaciers Southern and Northern Inylchek adjacent to the Merzbacher Lake - А. Shakirov (Лëд и снег)
Results of areal magnetometric investigation of glaciers South and North Enilchek located in the vicinity of the Merzbaher Lake are presented. These stud- ies resulted in finding of the bow-shaped rock bar (riegel) under the South Enilchek Glacier that became one of causes to turn its right flows toward the Merz- bacher Lake. Under the North Enilchek glacier the horseshoe-shaped riegel ledge was also detected, and that one created a barrier to accumulation of bottom sediments and, thus, formed a distinctive soil alluvial dam, which promoted formation of rather wide interface between upper and lower parts of the Merz- bacher Lake.